On local gradient estimates for anisotropic elliptic and parabolic equations - Skrypnik, I.I.; Skrypnik, S.V. (Труды Института прикладной математики и механики, 2012)
It is considered wide class of anisotropic elliptic and parabolic equations. Sharp local pointwise estimates for gradient of solutions of such equations are established. Рассмотрены широкие классы анизотропных эллиптических и параболических уравнений. Получены точные оценки для градиентов решений таких уравнений. Розглянуто широкi класи анiзотропних елiптичних та параболiчних рiвнянь. Отримано точнi оцiнки градiєнтiв розв’язкiв таких рiвнянь.